2013
DOI: 10.1111/jsr.12032
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress undermines the compensatory sleep efficiency increase in response to sleep restriction in adolescents

Abstract: SUMMARYTo investigate the effects of real-life stress on the sleep of adolescents, we performed a repeated-measures study on actigraphic sleep estimates and subjective measures during one regular school week, two stressful examination weeks and a week's holiday. Twenty-four adolescents aged 17.63 AE 0.10 years (mean AE standard error of the mean) wore actigraphs and completed diaries on subjective stress, fatigue, sleep quality, number of examinations and consumption of caffeine and alcohol for 4 weeks during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 30 publications
3
43
1
Order By: Relevance
“…34 In other studies, older Dutch adolescents who used objective actigraphy to record their sleep showed no association between caffeine drinks consumed and TST. 56 In a U.S. sample, there was no significant difference in caffeine use between adolescents who slept <8 h or >8 h per night. 38 In a South African sample, caffeine was not correlated with TST.…”
Section: Caffeine and Tstmentioning
confidence: 95%
“…34 In other studies, older Dutch adolescents who used objective actigraphy to record their sleep showed no association between caffeine drinks consumed and TST. 56 In a U.S. sample, there was no significant difference in caffeine use between adolescents who slept <8 h or >8 h per night. 38 In a South African sample, caffeine was not correlated with TST.…”
Section: Caffeine and Tstmentioning
confidence: 95%
“…Less TST as caffeine consumption increased is consistent with other literature in children [9][10][11] ; similarly, no relationship with SOL was found in a sample of adolescents. 34 With regard to broader sleep problems, sleep routine and restless sleep, specifically in relation to caffeine intake, have not been investigated previously in any age group. Li and colleagues 32 found an increase in the number of nocturnal awakenings when children aged 5 to 12 years consumed caffeine after 6:00 pm.…”
Section: Discussionmentioning
confidence: 99%
“…Good sleep requires individuals to have a sense of safety, security, and predictable environments. If individuals feel threatened or worried, they may be vigilant and ruminate, leading to short, fragmented sleep (Astill, Verhoeven, Vijzelaar, & Van Someren, 2013; Hall, Dahl, Dew, & Reynolds, 1995). Short, fragmented sleep is likely to be perceived as low quality and result in daytime sleepiness compared to longer, less fragmented sleep.…”
Section: Introductionmentioning
confidence: 99%